Berberine: a comprehensive Approach to combat human maladies. Issue 1 (31st December 2023) - Mushtaq, Zarina; Imran, Muhammad; Saeed, Farhan; Imran, Ali; Ali, Shinawar Waseem; Shahbaz, Muhammad; Alsagaby, Suliman A.; Guerrero Sánchez, Yolanda; Umar, Maryam; Hussain, Muzzamal; Al Abdimonem, Waleed; Al Jbawi, Entessar; et al.
ABSTRACT: Berberine is a metabolite of many medicinal plants. Chemically, berberine belongs to the isoquinoline alkaloids family. The roots of plants grown at lower elevations have a higher concentration of berberine as compared to plants grown at higher elevations. Berberine is a natural substance, which is now among the patent pharmaceuticals for reducing chronic disorders and malignancies. Berberine is also classified as a nutraceutical. Nutraceuticals have been associated with various health benefits via modifying microRNA (miR) expression systems, apoptosis, gene activity, chemical signals/pathways and activation of transcription factors thus aiding in the prevention from various ailments. The pharmacokinetic studies revealed that berberine is poorly absorbed via intestinal walls therefore, its concentration level is extremely low in body fluid. However, the quantity of berberine and its active derivatives in organs is higher as compared to blood as it stably present in tissues. Berberine has an effective role in the body as an anticancer, antidiabetic, antiobesity, antioxidant, antiinflammatory, neuroprotective, hepatoprotective, antiaging and cardioprotective agent. In this review, the therapeutic potentials of berberine are discussed to understand its nutraceutical importance.